2006
DOI: 10.1086/499419
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Solar Protons on 1989 October 22: Injection and Transport along Both Legs of a Closed Interplanetary Magnetic Loop

Abstract: Worldwide neutron monitor observations of relativistic solar protons on 1989 October 22 have proven puzzling, with an initial spike at some stations followed by a hump with bidirectional flows and a very slow decay. We analyze data from polar monitors, which measure the directional distribution of solar energetic particles (mainly protons) at rigidities of ¥ 1-3 GV. The inferred density and anisotropy are simultaneously fit by simulating the particle transport for various magnetic field configurations and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 66 publications
1
58
0
1
Order By: Relevance
“…Magnetic mirroring, as evidenced by bidirectional flow of relativistic particles following intense solar activity, has been previously reported by Cramp et al (1997a) and Bieber et al (2002) and bidirectional flow in a closed interplanetary magnetic loop has been reported by Ruffolo et al (2006).…”
Section: State Of the Interplanetary Medium: Gle 69mentioning
confidence: 67%
“…Magnetic mirroring, as evidenced by bidirectional flow of relativistic particles following intense solar activity, has been previously reported by Cramp et al (1997a) and Bieber et al (2002) and bidirectional flow in a closed interplanetary magnetic loop has been reported by Ruffolo et al (2006).…”
Section: State Of the Interplanetary Medium: Gle 69mentioning
confidence: 67%
“…Some solar particle events were observed inside magnetic clouds of previous CMEs, and the particle transport was correspondingly modeled in a kind of interplanetary magnetic loop (Kocharov et al 2005;Ruffolo et al 2006). However, for the 2003 November 2 event, an interplanetary magnetic cloud has not been identified with in situ plasma data, even though the solar wind was strongly distorted by previous solar eruptions (Appendix A).…”
Section: Interplanetary Transport Modelingmentioning
confidence: 99%
“…To our knowledge a double-injection scenario could never be proven unambiguously, although it was often presumed (e.g., Richardson & Cane 1996;Leske et al 2012). Only modeling results of neutron monitor measurements of the 22 October 1989 event by Ruffolo et al (2006) strongly suggested such a scenario.…”
Section: Introductionmentioning
confidence: 90%